A Theorem on Utilitarianism - Maskin, E. (Review of Economic Studies, 1978)
Journal Article A Theorem on Utilitarianism Get access Eric Maskin Eric Maskin Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 1, February 1978, Pages 93–96, https://doi.org/10.2307/2297086 Published: 01 February 1978